To the problem of the methodological foundations of the philosophy of history - Novikova, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The issue focuses on explication of the conceptual and methological foundations of the philosophy of history such as the special aspects of how man is examined in philosophical science. The author takes under consideration the main approaches to the comprehension of society which are universalism, individualism, particularism and analyzes relevant programms of the socio-historical reality exploration. The methodological foundation of these approaches concerns to the extrapolation of the philosophical notions «singular – general – particular» to the interpretations of social dynamics. Besides, the article is devoted to the explication of status of man in history and to the specification of the socio-historical entity, space and time.